Dynamic Response of Semisubmersibles with Damaged Mooring Lines - Kurian, V.J. (2012)
For the final design of moored floating structures, the design regulations require a complete assessment of the damaged mooring conditions. In this study, a twin hulled six column semi-submersible has been modeled using Froude’s law of similitude with a scale of 1:100. In order to investigate the effects of single line failure of the restraining system on the motion and the intact line responses, four seakeeping tests have been conducted in head and beam random seas. Results indicate that the platform migrates to new mean position with a remarkable transient response directly following the line failure. KEYWORDS: Mooring line loss; Physical modelling; Damage conditions; Dynamic response; Semi-submersible model; Wave basin testing.